Prostitution is Not Work: A Trade Unionist's Perspective. Issue 2 (December 2017) - Kaur, Amarjeet
As Secretary of the All India Trade Union Congress (AITUC), the oldest trade union federation in India and one of the five largest, the author argues that prostitution is a continuum of abuse of women, who are already bereft of their rights as workers, and whose choices are limited due to their marginalization as females in the patriarchal and feudal society of India. Women experience various types of exploitation in the regular industries, and are vulnerable to their labour being exploited because of their unequal education and unequal access to resources. The author locates instances of such exploitation, in both the organized and unorganized sector. She explains why her trade union has rejected the the use of the term 'sex-worker', for prostitution.